Transnational civil society and the World Bank : investigating civil society's potential to democratize global governance - Pallas, Christopher L.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
Transnational civil society is often seen as an important contributor to the democratization of global governance. In their engagement with the World Bank, however, transnational civil society organizations prioritize pre-existing mission over responsiveness to claimed stakeholders and undercut the authority of developing country governments.
Keywords: Science; Science; Science, general